Constructing the Early Mesozoic Gangdese Crust in Southern Tibet by Hornblende-dominated Magmatic Differentiation - Xu, Wei; Zhu, Di-Cheng; Wang, Qing; Weinberg, Roberto F; Wang, Rui; Li, Shi-Min; Zhang, Liang-Liang; Zhao, Zhi-Dan (Journal of petrology, 2019)
Abstract Igneous complexes with a wide variety of lithologies in continental magmatic arcs provide a critical insight into the composition and formation mechanism of continental crust. We report, for the first time, a systematic dataset for the petrology, mineralogy, geochronology, and geochemistry of the Cuijiu Igneous Complex in the eastern Gangdese Arc of southern Tibet. This complex includes a wide variety of rocks from ultramafic–mafic and felsic cumulates to mafic to felsic non-cumulate plutonic rocks. Cumulate and non-cumulate rocks can be distinguished by combining petrography and bulk-rock composition. Titanite and zircon U–Pb dating of 15 samples shows that the varying lithologies within this complex crystallized contemporaneously at c. 200 Ma. The non-cumulate plutonic rocks were formed through hornblende-dominated fractional crystallization from cogenetic primitive basaltic magmas, which were derived from partial melting of a mantle wedge metasomatized by subduction-related fluids. The ultramafic–mafic and felsic cumulates have similar isotopic compositions and crystallization order of minerals to the non-cumulate plutonic rocks, representing complementary compositions of the fractional crystallization processes. Petrological and geochemical signatures call upon two-step fractional crystallization as the dominant process to generate the Gangdese Arc during the Early Mesozoic. The assemblage and crystallization order of minerals, as well as Al-in-Hb geobarometry, reveal that the c. 200 Ma Cuijiu Igneous Complex crystallized at a range of pressures between 10 and 2·5 kbar. This result allows us to propose that the Early Mesozoic Gangdese crust had a normal thickness (∼35 km), in which the middle to lower part (20–35 km) was dominated by hornblende-rich rocks with minor diorites and tonalites intruding metamorphosed Late Paleozoic igneous rocks, followed upward by a thick granitoid batholith (4–20 km) and by volcano-sedimentary rocks (0–4 km).